(untitled) (Journal of Medicine, 2022)
Background: Erythema induratum of Bazin is a rare manifestation of cutaneous tuberculosis. It may mimic some systemic disorders like sarcoidosis, poly arteritis nodosa, lymphoproliferative disorder, Histoplasmosis, and lupus profundus. Case Presentation: A 38-year young female, diabetic, and hypertensive presented with multiple painful skin lesion over anterior part of her leg for 3 months. These skin lesion used to appear as painful erythematous nodules of variable size and shape over the anterior and lateral aspects of both legs that became ulcerate, healed with hyperpigmentation. On examinations, all of her systemic examinations revealed unremarkable except skin lesion. Punch biopsy from skin lesion revealed lobular panniculitis with granuloma suggestive of erythema induratum and MTB gene Xpert from skin lesion found positive. Thereafter, she was put on anti TB therapy six-month regimens according to the national TB guideline, Bangladesh. After 2 and half months of treatment, her skin lesion disappeared. Conclusion: In a TB prevalent country, erythema induratum should be kept in differential diagnosis along with others. As it is usually underdiagnosed or misdiagnosed because of the absence of typical clinical features of TB, therefore comprehensive investigations like skin biopsy with histopathology, detecting DNA of Mycobacterium tuberculosis by PCR, positive Mantoux test are the cornerstone for confirmatory diagnosis. J MEDICINE 2022; 23: 165-168